JS08.7.A Integrative analysis of longitudinal genomic and non-genetic mechanisms of radiotherapy-resistance in glioma. (5th September 2022) - Kocakavuk, E; Varn, F S; Johnson, K C; Verhaak, R G W
Abstract: Background: Radiotherapy (RT) is a mainstay in the treatment of glioma patients, but RT-resistance is common. We have recently identified RT-associated genomic small deletion signatures, marking tumors that have developed resistance. Here, we used longitudinal molecular profiles to explore non-genetic mechanisms of RT-resistance. Material and Methods: We have analyzed the multi-omic Glioma Longitudinal Analysis (GLASS) dataset, integrating DNA and RNA sequencing datasets from primary and post-treatment gliomas. Results: We classified tumors as harboring temozolomide-associated hypermutation based on mutational burden increase (HM), and RT-associated signature based on small deletion burden increase (RTscars). By deconvoluting RNA profiles into cell state fractions, we observed an increase of a proliferating stem-like (PSL) cell state in 50% of patients with a RTscars + signature which was significantly higher than RTscars - /HM - patients (P=8e-04, Fisher's exact). PSL cell state increase associated with worse overall survival outcomes (P=1.5e-03, log-rank). We observed a significant correlation between the expression change of E2F cell cycle regulator genes (R=0.91, P=6.7e-04, Pearson) and EZH2 (R=0.81, P=8.3e-03) with the increase in the PSL cell state, nominating the E2F/EZH2-pathway as regulator of the PSL cell state. Furthermore, the RTscars signature was associated with an increase in frameshift neoantigens and significantly higher neoantigen burden at recurrence (P=2.4e-02, Kruskal-Wallis). This was accompanied by a significantly higher post-treatment T-cell fraction in RTscars + tumors (P=8.2e-04, Wilcox), suggesting an increased T-cell infiltration in these patients. Conclusion: Our analyses revealed a longitudinal increase in the proliferating stem-like cell state associated with RT-resistance and nominates the cell cycle pathway as an actionable target. The RT-associated deletion signature (RTscars) correlated with increased frameshift-neoantigens and T-cell fractions at recurrence, suggesting a potential benefit of a combinatorial immune-targeted therapy in this specific patient population.